ANALISIS PENGARUH DANA DESA DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP INDEKS PEMBANGUNAN MANUSIA DI JAWA TENGAH - Gallyn Ditya Manggala; Sheny Yulianty (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2024)
This study aims to analyze the influence of Village Funds and Gross Regional Domestic Product (GDP) on the Human Development Index (HDI) in Central Java Province. This study uses a panel data regression model with a coverage of 29 districts in Central Java during the 2016-2020 period. The results of the study show that Village Funds and GDP have a positive and significant influence on HDI. The Regression Coefficient of Village Funds of 2.96E-10 indicates a positive and significant influence, which means that every increase in one unit of Village Funds will increase HDI by 2.96E-10, assuming the other variables remain constant. GDP was also found to have a significant influence on HDI in Central Java, with a regression coefficient value of 111.4025, indicating that every increase in one unit of GDP will increase HDI by 111.4025.